A CASE STUDY ON THE IMPACT OF SKILL-BASED EDUCATION ON YOUTH UNEMPLOYMENT IN PUBIC SECTOR UNIVERSITIES - Asma Ishaq (Policy Research Journal, 2025)
The high unemployment rate among the youths persists in Pakistan mainly the graduate from public sector universities. The policy concern of this study is to analyses the effectiveness of skill-based education in addressing the threat of high unemployment among youths in these institutions. 100 graduates from each five universities were selected, using a structured questionnaire developed from the literature review section; following a quantitative research design. Hence, the research narrows down its main concerns on the connection between skills based trainings, employment and labor market absorption of graduates. These findings show that new candidates who pursued skill based education have higher probabilities to find employment than those trained under theory based curriculum. The presented results raise the need to incorporate workplace competencies into curriculum to align learning with economic realities. Consequently, this research offers policy recommendations for policymakers, educators, and stakeholders to tackle youth-unemployment.